KESIAPAN GURU DALAM IMPLEMENTASI KURIKULUM 2013 DITINJAU DARI KEPEMIMPINAN KEPALA SEKOLAH, KOMPETENSI PROFESIONAL, DAN KREATIVITAS GURU SEKOLAH MENENGAH PERTAMA DI KECAMATAN TERNATE TENGAH TAHUN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine the effect of independent variables of school leadership, professional competence, and creativity of the teacher to the dependent variable in the teacher preparation curriculum implementation in the district in 2013 Junior High Middle Ternate Year 2013/2014. The population of this study are all teachers of SMP Negeri 6 SMP 7, SMP Al-Khairat and Islamic junior totaled 208 teachers and the sample of 137 teachers based on the nomogram table Herrera King. This type of research is correlative with the quantitative approach. The results showed there is a significant positive effect between school leadership, professional competence, and creativity of teachers to the readiness of teachers in curriculum implementation in the district in 2013 Junior High Middle Ternate either simultaneously or partially. Based on the value of the effective contribution of the independent variables showed the most dominant variable in the readiness of teachers in curriculum implementation in 2013 is a professional competence variables.